IMPLEMENTASI MODEL FINANSIAL DISTRES PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI IDX TAHUN 2015-2017 - Zakiyah, Tuti; Windasari, Wahyuni (P4M STIE Putra Bangsa, 2020)
Manufacturing Company is a sample of this study, the dependent variable used in this study is a binary variable, namely whether the company is in financial distress or non-financial distress. Hypothesis testing uses binary logistic regression (Binary Logistic Regression) because the dependent variable is a combination of metric and non-metric (nominal). The model used is the Altman Z-Score model, Springate S-Score, Grover G-Score, Zmijewski X-Score, and univariate models. Of the five models, the best model is the Springate S-Score with a Nagelkerke R2 value of 0.582. the second is, Zmijewski X-Score with a value of 0.227 and the third best is the Univariate Model with a value of 0.042. Of the three best models, namely the Springate S-Score, Zmijewski X-Score and the Univariate Model. The implementation is that the ratios in these models are very important to be considered by companies as a sensitivity tool so that companies do not experience financial distress. ratios that are often used are ratios related to the company's ability to manage and produce net working capital, sales, debt and ability to generate profits from sales and profits from assets.